Hereditary spastic paraplegia is a novel phenotype for germline de novo ATP1A1 mutation. Issue 3 (5th December 2019) - Stregapede, Fabrizia; Travaglini, Lorena; Rebelo, Adriana P.; Cintra, Vivian Pedigone; Bellacchio, Emanuele; Bosco, Luca; Alfieri, Paolo; Pro, Stefano; Zuchner, Stephan; Bertini, Enrico; Nicita, Francesco
Abstract: Dominant mutations in ATP1A1, encoding the alpha‐1 isoform of the Na + /K + ‐ATPase, have been recently reported to cause an axonal to intermediate type of Charcot‐Marie‐Tooth disease (ie, CMT2DD) and a syndrome with hypomagnesemia, intractable seizures and severe intellectual disability. Here, we describe the first case of hereditary spastic paraplegia (HSP) caused by a novel de novo (p.L337P) variant in ATP1A1 . We provide evidence for the causative role of this variant with functional and homology modeling studies. This finding expands the phenotypic spectrum of the ATP1A1 ‐related disorders, adds a piece to the larger genetic puzzle of HSP, and increases knowledge on the molecular mechanisms underlying inherited axonopathies (ie, CMT and HSP). Abstract : We describe the first case of hereditary spastic paraplegia (HSP) caused by a novel de novo (p.L337P) variant in ATP1A1. Evidences for the causative role of this variant are provided through functional and homology modeling studies. This finding expands the phenotypic spectrum of the ATP1A1‐related disorders, adds a small piece to the large genetic puzzle of HSP and increases knowledge on the molecular mechanisms underlying inherited axonopathies.